2010
DOI: 10.1002/jhm.805
|View full text |Cite
|
Sign up to set email alerts
|

Redefining readmission risk factors for general medicine patients

Abstract: BACKGROUND:Readmissions are costly both financially for our healthcare system and emotionally for our patients. Identifying factors that increase risk for readmissions may be helpful to focus resources to optimize the discharge process and reduce avoidable readmissions.OBJECTIVE:To identify factors associated with readmission within 30 days for general medicine patients.METHODS:We performed a retrospective observational study of an administrative database at an urban 550‐bed tertiary care academic medical cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
162
9
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(187 citation statements)
references
References 34 publications
14
162
9
2
Order By: Relevance
“…Allaudeen et al showed in multivariable analysis of more than 10,000 consecutive general medicine patients in a tertiary care academic medical center that cancer with or without metastasis was a factor associated with readmission. 5 A retrospective single-institution cohort study by Schairer et al similarly found a higher rate of readmission for patients with primary and metastatic tumors of the spine. In their study, they reported a readmission rate of 14.2% and also confirmed that infectious complications were the most common cause for readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Allaudeen et al showed in multivariable analysis of more than 10,000 consecutive general medicine patients in a tertiary care academic medical center that cancer with or without metastasis was a factor associated with readmission. 5 A retrospective single-institution cohort study by Schairer et al similarly found a higher rate of readmission for patients with primary and metastatic tumors of the spine. In their study, they reported a readmission rate of 14.2% and also confirmed that infectious complications were the most common cause for readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Almost 20% of Medicare beneficiaries are readmitted within 30 days of discharge costing about $15 billion annually [7][8][9] , of which about $12 billion is potentially avoidable [10] . Certain patient characteristics, such as demographic factors, medical history, and diseases and comorbidities, have been found to increase the likelihood of a readmission [7,11] .…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that heart attack, pneumonia, and congestive heart failure are three key diagnoses that require special attention due to higher than average readmission rates [17] . Allaudeen and colleagues found that having comorbidities (congestive heart failure, renal disease, cancer) is positively associated with readmissions [8] . Rau identified heart failure as the most common condition affecting readmissions, with hospitals serving the poorest Medicare patients being nearly three times as likely as others to have substantially high readmission rates for this condition [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with low socioeconomic status (SES) are up to 43% more likely to require readmission than their higher-SES counterparts, 8,9 and qualitative data has described unique challenges faced by low-SES patients during transition. 2 Our objectives were to understand the transition experiences of readmitted patients and to compare these experiences across SES and diagnostic categories.…”
mentioning
confidence: 99%